Empowering MSMEs agility: A microfoundational perspective linking human capital and dynamic managerial capability - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; I Made Hedy Wartana; I Ketut Yudana Adi (Universitas Ahmad Dahlan, 2026)
Human capital, dynamic managerial capability, and organizational agility are increasingly recognized as key enablers of strategic adaptation for micro, small, and medium enterprises, particularly in volatile environments. However, the pathway through which human capital fosters organizational agility remains insufficiently examined. This study investigates the mediating role of dynamic managerial capability in the relationship between human capital and organizational agility within micro, small, and medium enterprises in Bali, Indonesia. Adopting a quantitative approach, data were collected from 131 micro, small, and medium enterprises managers using structured questionnaires, employing a proportionate random sampling technique. The relationships among constructs were analyzed using variance-based structural equation model-partial least square, including measurement and structural model evaluation. The findings indicate that while human capital strongly influences dynamic managerial capability, its direct effect on organizational agility is weak. Mediation analysis confirms that dynamic managerial capability mediates the effect of human capital on agility. These results underscore that organizational agility in micro, small, and medium enterprises is realized not merely through the presence of human capital, but through its activation via dynamic managerial capability. This research provides empirical evidence for the microfoundational role of dynamic managerial capability in translating human resources into agile organizational performance, advances strategic capability theory, and offers practical insights for capability development in emerging economies.